Pengenalan dan pengendalian hama dan penyakit utama tanaman cabai di Desa Sungai Geringging Kecamatan Kampar Kiri Kabupaten Kampar - Hafiz Fauzana; Rusli Rustam; Nelvia Nelvia; Yetti Elfina; Wardati Wardati; Murniati Murniati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Chili plants are one of the horticultural commodities that have economic value and are widely planted in Sungai Geringging Village, Kampar Kiri District, Kampar Regency. The main obstacle in achieving the quantity and quality of chili production is the attack of pests and diseases. This service aims to provide knowledge to chili farmers in Sungai Geringging Village about the types of pest and disease that attack chilies, symptoms of attack, and methods of control. The extension methods are lectures, questions and answers, discussions, demonstrations and practices with regard to chili plants. Extension is in the form of indoor presentation using LCD and in-focus tools by demonstrating the types of pest and disease that attack chilies and their attack symptoms, discussion and question and answer about pests and diseases of chili plants and their control techniques. Service programs in the form of counseling and demonstrations have been very well responded by chili farmers, counseling and demonstrations with material on how to introduce and control chili pests have never been received, plus in the cultivation of chili plants the obstacles that are often faced by farmers are problems with pests and diseases therefore participating farmers pay closer attention.